CHILDREN TALK - Khoirul Huda (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2016)
Children do not trade in their immature speech for mature speech all at once. They always go through a sequence of stages of language use, moving from simple to complex. they imitate the nouns and verbs and sentence structures of others around them; they can fit their own words into these imitated structures to create novel sentences. But the facts of children's speech do not fit this explanation either. Children produce many sorts of grammatical constructions that they have not heard before. A two- year-old says,